Optimalisasi Kesehatan dan Gizi Lansia Melalui Penyuluhan dan Pendampingan Gizi di Kelurahan Cipadu Jaya: Optimizing Health and Nutrition of the Elderly through Nutrition Counseling and Assistance in Cipadu Jaya Village - Ngadiarti, Iskari; Muntikah, Muntikah; Noviani, Ani; Nixon, Aurasyifa Salsabila (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The percentage of the elderly population in RW 01, Cipadu Village, has increased, indicating that in 2023, this area has entered the era of an aging population, where the percentage of the population aged 60 and above is almost reaching 10% or more. The purpose of this community service is to raise awareness among the community about a healthy lifestyle to prevent non-communicable diseases, to practice the preparation of healthy drinks, and early detection of health status through anthropometry and stick test methods. The methods used in this community service include counseling with the theme